Analyzing the Impact of Significant Factors on Motivation and Accountability of Employees in the Supply Chain of Organization - Anwer Abbas Naser; Abbas Saad Hamada; Alaa Miran Hassein (International Journal of Supply Chain Management, 2019)
Undoubtedly, all efforts and behaviors are based on motives and goals. Motives and goals are two of the main internal and external factors that make people reach the destination to work. This article seeks to provide factors that influence the motivation and accountability of employees in the supply chain of organization. The results of the research showed that paying attention to employees' motivational factors and their needs and paying attention to individual differences of each employee is one of the most important factors. Which can be achieved in the productivity of human resources and one of the essential conditions for achieving the goal in every way is to provoke and motivate and respond to the people who do it. Factors like meritocracy, awarding rewards to better services, preventing and disrupting individual choices are one of the most important motivations and responses.